Benzothiazole-based compounds as potent endothelial lipase inhibitors. Issue 20 (15th October 2019) - Meng, Wei; Adam, Leonard P.; Behnia, Kamelia; Zhao, Lei; Yang, Richard; Kopcho, Lisa M.; Locke, Gregory A.; Taylor, David S.; Yin, Xiaohong; Wexler, Ruth R.; Finlay, Heather
Graphical abstract: Abstract: A series of benzothiazoles with a cyano group was synthesized and evaluated as endothelial lipase (EL) inhibitors for the potential treatment of cardiovascular diseases. Efforts to reduce molecular weight and polarity in the series led to improved physicochemical properties of these compounds, as well as selectivity for EL over hepatic lipase (HL). As a benchmark compound, 8i demonstrated potent EL activity, an acceptable absorption, distribution, metabolism and elimination (ADME) profile and pharmacokinetic (PK) exposure which allowed further evaluation in preclinical animal efficacy studies.